2018
DOI: 10.1186/s40360-018-0221-6
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation down-regulates CYP3A4-catalysed drug metabolism in hemodialysis patients

Abstract: BackgroundRecent studies indicate that inflammation may also affect CYP3A4 activity. Associations of CYP3A4-mediated metabolism of quinine, with inflammatory biomarkers were investigated in patients undergoing maintenance hemodialysis (HD).MethodsA single dose of 100 mg quinine was given to 44 HD patients and the plasma concentration of quinine and its metabolite 3-OH-quinine were measured 12 h after drug intake. The ratios of quinine/3-OH-quinine and 4β-OH-cholesterol/cholesterol were used as markers of CYP3A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 45 publications
1
14
1
Order By: Relevance
“…In patients with COVID-19, the risks of drug–drug interactions involving psychotropic medications might be relevant. Firstly, the bioavailability and disposition of several psychotropic medications might be importantly affected by COVID-19-related systemic inflammation processes [ 65 ], impaired liver functioning [ 35 ], and abrupt smoking cessation [ 45 , 46 , 64 ]. Secondly, psychotropic medications and medical treatments can reciprocally affect each other’s plasma levels by inducing or inhibiting cytochrome P450 (CYP) activity to an extent which is poorly understood and hardly predictable [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…In patients with COVID-19, the risks of drug–drug interactions involving psychotropic medications might be relevant. Firstly, the bioavailability and disposition of several psychotropic medications might be importantly affected by COVID-19-related systemic inflammation processes [ 65 ], impaired liver functioning [ 35 ], and abrupt smoking cessation [ 45 , 46 , 64 ]. Secondly, psychotropic medications and medical treatments can reciprocally affect each other’s plasma levels by inducing or inhibiting cytochrome P450 (CYP) activity to an extent which is poorly understood and hardly predictable [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous publications have demonstrated that infection and more broadly inflammation decreased CYP3A activity, and in proportion to the severity of the disease 5,11,14,24,25 . Moreover, authors have shown that CYP3A4 activity was inversely correlated to CRP levels 26,27 . Surgery and cancer have also been associated with decreased CYP3A4 activity and increased serum levels of CRP and IL‐6, respectively 9,10 .…”
Section: Discussionmentioning
confidence: 99%
“…5,11,14,24,25 Moreover, authors have shown that CYP3A4 activity was inversely correlated to CRP levels. 26,27 Surgery and cancer have also been associated with decreased CYP3A4 activity and increased serum levels of CRP and IL-6, respectively. 9,10 Moreover, in patients with rheumatoid arthritis, when inflammation was reversed by tocilizumab, an anti-IL-6 receptor antibody, exposure to simvastatin was significantly reduced by half at 1 and 5 weeks after infusion.…”
Section: Discussionmentioning
confidence: 99%
“…However, data are still lacking to accurately describe the impact of each factor in this multifactorial change. The impact of inflammation on CKD patients has been independently investigated in only one study, using alprazolam as a probe drug for CYP3A4 activity ( Molanaei et al, 2018 ). The ratio of alprazolam to 4-hydroxyalprazolam correlated with CRP concentrations in 26 hemodialysis patients, suggesting the downregulation of CYP3A4 activity by inflammation.…”
Section: Pharmacological Consequences Of Inflammation-induced Metabolmentioning
confidence: 99%